APPLICATIONS ON MICROSOFT ACCESS DATA INFORMATION SYSTEM IN PT. SARJANA BUDI SATRIA - Tri Widodo; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 1999)
PT. Sarjana Budi Satria was established on October 9, 1991 one of its business is engaged in the provision of information services and dat homestay in Jakarta area. Process information that is still done manually created many obstacles such as statements that are  not timely, the contents of the reports are often wrong, the difficulty in updating and manipulation of data outhouse. For it is necessary to establish a database to generate input / output board which facilitates information services. That output include  the output data information and output board for the consumer for the company's monthly revenue reports. Inputs include inputs from the outhouse, territories and consumer data.